(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Ciphertext-Policy Attribute-Based Encryption (CP-ABE) has emerged as a promising cryptographic technique for enhancing data security and access control in cloud environments. This paper presents a comprehensive study on designing and implementing Secured Access Policies within CP-ABE frameworks. We propose a novel approach that combines attribute-based encryption with fine-grained access control, allowing data owners to specify intricate access policies for their encrypted data. Our solution addresses the challenges of scalability, key management, and policy expressiveness in cloud-based scenarios. We provide a detailed analysis of the proposed Secured Access Policy framework, highlighting its advantages and practical implications.